2009
DOI: 10.3233/jad-2009-0996
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression as Peripheral Biomarkers for Sporadic Alzheimer's Disease

Abstract: Alzheimer's disease (AD), the most common cause of dementia, is a progressive neurodegenerative disease. At present, diagnosis of AD is rather late in the disease. Therefore, we attempted to find peripheral biomarkers for the early diagnosis of AD. We investigated the profiles of 33 genes, previously found by our group to have altered expression in postmortem brains of AD. The gene profiles were studied via quantitative-real-time-reverse-transcription-polymerase-chain-reaction, in whole blood samples (collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 7 publications
0
46
0
1
Order By: Relevance
“…Few animal studies which have been focused on the glutamate neurotransmission in the STZ-icv animal models revealed, in general, changes similar to those found in AD patients. An increased expression of glutamate transporter mRNA has been found previously in the STZ-icv rats (Grünblatt E et al 2004), and deficits in hippocampal synaptic transmission and long-term potentiation (LTP) observed in the STZ-icv treated rats were recently suggested to be mainly due to the postsynaptic mechanisms and were accompanied by changes in the expression and function of glutamate alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptors (Shonesy et al 2012). Furthermore, LTP deficits were found to correlate with decreased expression of NMDA receptor subunits NR2A and NR2B, which could be related to the reduction of brain derived neurotrophic factor (BDNF) in the STZ-icv rat model (Shonesy et al 2012).…”
Section: Nmda Receptor Antagonistsmentioning
confidence: 74%
“…Few animal studies which have been focused on the glutamate neurotransmission in the STZ-icv animal models revealed, in general, changes similar to those found in AD patients. An increased expression of glutamate transporter mRNA has been found previously in the STZ-icv rats (Grünblatt E et al 2004), and deficits in hippocampal synaptic transmission and long-term potentiation (LTP) observed in the STZ-icv treated rats were recently suggested to be mainly due to the postsynaptic mechanisms and were accompanied by changes in the expression and function of glutamate alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptors (Shonesy et al 2012). Furthermore, LTP deficits were found to correlate with decreased expression of NMDA receptor subunits NR2A and NR2B, which could be related to the reduction of brain derived neurotrophic factor (BDNF) in the STZ-icv rat model (Shonesy et al 2012).…”
Section: Nmda Receptor Antagonistsmentioning
confidence: 74%
“…Moreover, it has been suggested that blood-based GEP can be used as a powerful tool for early diagnosis of certain solid cancer entities, [32][33][34][35][36] as well as infectious, 37,38 autoimmune, 39,40 and neurodegenerative 41 disease. Nevertheless, prospective clinical studies are still needed to validate these promising but still preliminary results in larger cohorts of patients or in individuals at risk for the respective diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The profiling of these genes was carried our four times in a period of one year in correlation to AD and it was found that the expression of HIST1H3E was correlated in a negative 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 14 manner to the MMSE scores, while. the expression of CNR2 showed some tendency to positively correlate with the decreased MMSE score (Grunblatt et al, 2009). …”
Section: Genetic Biomarkersmentioning
confidence: 99%